Becoming a Resilient Parent: Positive Psychology-Based Psychoeducation at the Parent Club of the Indonesian Children's Oncology Foundation - Tania Mursalim; Riana Sahrani; Pamela Hendra Heng (Green Publisher Indonesia, 2026)
Families of children with cancer experience significant emotional, physical, and social stressors, beginning at the diagnostic phase and continuing throughout the long-term treatment process. This condition can reduce hope, weaken perseverance, and disrupt the psychological capacity of parents in fulfilling their caregiving roles. This Community Service Program aimed to strengthen the psychological capacity of families through psychoeducation based on positive psychology, emphasizing the reinforcement of hope, resilience, and grit, as well as optimizing the role of the Parent Club (PC) of Yayasan Onkologi Anak Indonesia as a key pillar of community support for newly affected families. The program was conducted in a hybrid format and involved 87 participants, consisting of Parent Club members, parents of children currently undergoing cancer treatment, and community support facilitators. The effectiveness of the program was evaluated through pre-test and post-test measures completed by 65 participants. The results indicated a consistent increase in participants’ understanding across all measured indicators, reflected in a higher percentage of correct responses related to the concepts of resilience, hope, grit, and the meaning of parental toughness. This improvement illustrates a shift in participants’ perspectives from reactive responses toward more structured and adaptive interpretations of the caregiving process. These findings demonstrate that a psychoeducational approach incorporating reflective activities, expressive writing exercises, and participatory discussions is effective in enhancing parents’ psychological literacy and strengthening their emotional readiness to cope with the prolonged demands of caregiving.